The Cocoki Board as a Development of Javanese Script Flashcard Learning Media for Grade VII Students at SMP Negeri 2 Sidoharjo Sragen (Piwulang: Jurnal Pendidikan Bahasa Jawa, 2025)
This research is about learning media which has quite important meaning in the learning process, especially learning Javanese. Learning will be better assisted by presenting creative and innovative learning media. This research discusses flashcard learning media with the development of the "COCOKI" board as an intermediary in the Javanese script learning process. This learning media was designed with the aim of improving the ability to read Javanese script in class VII students of SMP Negeri 2 Sidoharjo Sragen for the 2024/2025 academic year. This research was carried out using an R&D design with the ADDIE model, namely analysis, design, development, implementation and evaluation. Data collection techniques in this research used interviews, validation sheets, and response questionnaires. The media board "COCOKI" received a response from class VII students of SMP Negeri 2 Sidoharjo Sragen for the 2024/2025 academic year as users, namely 99% which fell into the "very good" criteria. This research shows that flashcard learning media with the "COCOKI" board is easy to use and effective for introducing Javanese script to students. Provides benefits in increasing children's motivation to learn Javanese script. It has the advantages of portability (easy to carry) and ease of use by teachers and parents without special skills.